2022
DOI: 10.3847/2041-8213/ac6186
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of the RNA World in Space: Detection of (Z)-1,2-ethenediol in the Interstellar Medium, a Key Intermediate in Sugar Formation

Abstract: We present the first detection of (Z)-1,2-ethenediol, (CHOH)2, the enol form of glycolaldehyde, in the interstellar medium toward the G+0.693−0.027 molecular cloud located in the Galactic Center. We have derived a column density of (1.8 ± 0.1) × 1013 cm−2, which translates into a molecular abundance with respect to molecular hydrogen of 1.3 × 10−10. The abundance ratio between glycolaldehyde and (Z)-1,2-ethenediol is ∼5.2. We discuss several viable formation routes through chemical reactions from precursors su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 72 publications
4
62
0
Order By: Relevance
“…Besides HOCN, already reported by Brünken et al (2010) and Zeng et al (2018), we have provided the tentative detections towards this source of HCOCN and HOCH 2 CN (third detection in the ISM), and the detection of the three unsaturated C 4 H 3 N isomers (being the second source after TMC-1 in which all three isomers are identified). These detections confirm the rich reservoir of nitriles in space, and complete the list of prebiotic molecular precursors detected previously, including species directly involved in the synthesis of ribonucleotides such as glycolaldehyde (HCOCH 2 OH; Hollis et al, 2004;Requena-Torres et al, 2006;Beltrán et al, 2009;Jørgensen et al, 2012), urea (Belloche et al, 2019;Jiménez-Serra et al, 2020), hydroxylamine NH 2 OH (Rivilla et al, 2020), and 1,2ethenediol (Rivilla et al 2022a); of amino acids, such as amino acetonitrile (NH 2 CH 2 CN; Belloche et al, 2008;Melosso et al, 2020); and of lipids, such as ethanolamine (NH 2 CH 2 CH 2 OH; Rivilla et al, 2021a), and propanol (CH 3 CH 2 CH 2 OH; Jimenez-Serra et al 2022;Belloche et al 2022).…”
Section: Conclusion: Implications For the Rna-worldsupporting
confidence: 86%
See 1 more Smart Citation
“…Besides HOCN, already reported by Brünken et al (2010) and Zeng et al (2018), we have provided the tentative detections towards this source of HCOCN and HOCH 2 CN (third detection in the ISM), and the detection of the three unsaturated C 4 H 3 N isomers (being the second source after TMC-1 in which all three isomers are identified). These detections confirm the rich reservoir of nitriles in space, and complete the list of prebiotic molecular precursors detected previously, including species directly involved in the synthesis of ribonucleotides such as glycolaldehyde (HCOCH 2 OH; Hollis et al, 2004;Requena-Torres et al, 2006;Beltrán et al, 2009;Jørgensen et al, 2012), urea (Belloche et al, 2019;Jiménez-Serra et al, 2020), hydroxylamine NH 2 OH (Rivilla et al, 2020), and 1,2ethenediol (Rivilla et al 2022a); of amino acids, such as amino acetonitrile (NH 2 CH 2 CN; Belloche et al, 2008;Melosso et al, 2020); and of lipids, such as ethanolamine (NH 2 CH 2 CH 2 OH; Rivilla et al, 2021a), and propanol (CH 3 CH 2 CH 2 OH; Jimenez-Serra et al 2022;Belloche et al 2022).…”
Section: Conclusion: Implications For the Rna-worldsupporting
confidence: 86%
“…In the last decades, and especially in the last years, astrochemistry has shown that interstellar chemistry is able to synthesize building blocks of key biomolecules. Several of the precursors of ribonucleotides spotted by the prebiotic experiments in the laboratory have been detected in the ISM, like cyanoacetylene (HC 3 N, Turner 1971), cyanamide (NH 2 CN, Turner et al, 1975), glycolaldehyde (CH 2 OHCHO, Hollis et al 2004, urea (NH 2 CONH 2 , Belloche et al 2019), hydroxylamine (NH 2 OH, Rivilla et al 2020), and 1,2-ethenediol ((CHOH) 2 ; Rivilla et al 2022a). Among the key simple molecular precursors required for the RNA world, numerous works have stressed the dominant role of a particular family of compounds, nitriles, which are molecules with the C + N moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Besides HOCN, already reported by Brünken et al (2010) and Zeng et al (2018), we have provided the tentative detections towards this source of HCOCN and HOCH 2 CN (third detection in the ISM), and the detection of the three unsaturated C 4 H 3 N isomers (being the second source after TMC-1 in which all three isomers are identified). These detections confirm the rich reservoir of nitriles in space, and complete the list of prebiotic molecular precursors detected previously, including species directly involved in the synthesis of ribonucleotides such as glycolaldehyde (HCOCH 2 OH; Hollis et al 2004;Requena-Torres et al 2006;Beltrán et al 2009;Jørgensen et al 2012), urea (Belloche et al 2019;Jiménez-Serra et al 2020), hydroxylamine NH 2 OH (Rivilla et al 2020), and 1,2-ethenediol (Rivilla et al 2022a); of amino acids, such as amino acetonitrile (NH 2 CH 2 CN; Belloche et al 2008;Melosso et al 2020); and of lipids, such as ethanolamine (NH 2 CH 2 CH 2 OH; Rivilla et al 2021a), and propanol (CH 3 CH 2 CH 2 OH; Jimenez-Serra et al 2022;Belloche et al 2022).…”
Section: Conclusion: Implications For the Rna-worldsupporting
confidence: 83%
“…In the last decades, and especially in the last years, astrochemistry has shown that interstellar chemistry is able to synthesize building blocks of key biomolecules. Several of the precursors of ribonucleotides spotted by the prebiotic experiments in the laboratory have been detected in the ISM, like cyanoacetylene (HC 3 N, Turner 1971), cyanamide (NH 2 CN, Turner et al 1975), glycolaldehyde (CH 2 OHCHO, Hollis et al 2004, urea (NH 2 CONH 2 , Belloche et al 2019), hydroxylamine (NH 2 OH, Rivilla et al 2020), and 1,2-ethenediol ((CHOH) 2 ; Rivilla et al 2022a). Among the key simple molecular precursors required for the RNA world, numerous works have stressed the dominant role of a particular family of compounds, nitriles, which are molecules with the C N moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of the so-called interstellar Complex Organic Molecules (COMs, carbon-bearing species containing at least 6 atoms [ 16 ]) can be used to support this theory in providing useful hints on the RNA hypothesis. In fact, the simplest species mentioned by both Becker et al [ 7 ] and Powner et al [ 4 ] have been already detected in the interstellar medium (ISM): cyanoacetylene [ 17 ], cyanamide [ 18 ], hydroxylamine [ 19 ], glycolaldehyde [ 20 ] and its tautomer ethenediol [ 21 ], and urea [ 22 ]. Another important piece of information is the very recent observation of ring molecules and polycyclic aromatic hydrocarbons in the ISM [ 23 , 24 , 25 , 26 ], which indicates that the chemical complexity found in astronomical objects by far exceeds the expectation and demands searches of larger and more complex COMs, also including aromatic species [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%